2018
DOI: 10.1111/acps.12915
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of improved recognition of happy faces after erythropoietin treatment in bipolar disorder

Abstract: Together with previous findings, the present observation suggests that increased dorsal prefrontal attention control is a common mechanism of EPO-associated improvements across several cognitive domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In addition, as left and right PFCs are known to differentially modulate the down-stream limbic areas ( Cerqueira et al, 2008 ), EPO-induced enhancement of synaptic inhibition in the left PrL would down-regulated the down-stream HPA axis, and EPO-induced reduction of synaptic inhibition in the right PrL would then enhance the down-stream hippocampal activity and plasticity (illustrated in Graphic abstract). Thus, the lateralized EPO effect in the present study might contribute to the beneficial effects of EPO under stress as well as by mental disorders ( Czéh et al, 2018 ; Ehrenreich et al, 2008 , 2007b ; 2007a ; Miskowiak, 2017 ; Miskowiak et al, 2018 , 2010 ).…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, as left and right PFCs are known to differentially modulate the down-stream limbic areas ( Cerqueira et al, 2008 ), EPO-induced enhancement of synaptic inhibition in the left PrL would down-regulated the down-stream HPA axis, and EPO-induced reduction of synaptic inhibition in the right PrL would then enhance the down-stream hippocampal activity and plasticity (illustrated in Graphic abstract). Thus, the lateralized EPO effect in the present study might contribute to the beneficial effects of EPO under stress as well as by mental disorders ( Czéh et al, 2018 ; Ehrenreich et al, 2008 , 2007b ; 2007a ; Miskowiak, 2017 ; Miskowiak et al, 2018 , 2010 ).…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, an increase in cognitive performance upon EPO in patients with chronic progressive multiple sclerosis has been occurred independently of changes in hemoglobin levels, and persisted for months after termination of EPO treatment ( Ehrenreich et al, 2008 , 2007a ). Furthermore, EPO has also been shown to improve the cognitive ability in patients with mood disorder ( Miskowiak, 2017 ; Miskowiak et al, 2018 , 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…Bipolar disorder (BD) is an emotional disorder characterized by emotional instability [1,2], the main symptoms of which are emotional processing disorders [3,4]. While previous studies have found that patients with BD have mood-recognition disorder during remission, which appears as defective emotion recognition, other reports suggest that patients may have complete emotional perception [5].…”
Section: Introductionmentioning
confidence: 99%